PEMUPUKAN BAHAN ORGANIK UNTUK PERTUMBUHAN DAN HASIL UMBI TALAS SUTRA - Ridwan Diaguna; Edi Santosa; Candra Budiman; Ahmad Zamzami; Okti Syah Isyani Permatasari; Aldi Kamal Wijaya (Jurnal AGROSAINS dan TEKNOLOGI, 2022)
Indonesia has a great taro diversity and had been utilized for long time. Taro has more competitiveness including high nutrition, wide adaptation, and ease for cultivation, further, it’s very potential to be the future food and create new economical value. The objective of the research was to obtain the organic manure fertilizer effect on sutra taro variety growth and yield. The research was conducted for eight months from January till August 2021 at Leuwikopo Farm, Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University. A Completely Randomized Block Design (CRBD) with five replications and four-level organic manure treatments (0.25 kg, 0.5 kg, 0.75 kg, and 1.00 kg per plant) was applied. Taro growth, corm characters, and yields were affected by organic manure fertilizer dose. The dose of 0.75-1.00 kg/plant (equivalent to 15-20 ton/ha) showed the highest growth, corm characters and yields more than the lower doses. Taro “Sutra variety” cultivation by fully using organic manure fertilizers is very potential to be encouraged.